Investigation on structure of TeO2-B2O3-SiO2-Al2O3-KF glasses - Phan, Van Do (H. : ĐHQGHN, 2020)
Borotellurite glasses were prepared by melt quenching technique. Amorphous nature of samples was confirmed through X-ray diffraction (XRD) patterns. Effect of B2O3 content on the structure of glass network was studied through Fourier-transform infrared spectroscopy (FTIR) spectra. Optical band gap and Urbach energy were found from analysis of optical absorption spectra. Thermal studies were carried out by using Differential thermal analyzer (DTA) measurements.